Nymphaea pubescens Induces Apoptosis, Suppresses Cellular Oxidants-Related Cell Invasion in B16 Melanoma Cells - Parichaya Aimvijarn; Teerapat Rodboon; Witchuda Payuhakrit; Prasit Suwannalert (Tabriz University of Medical Sciences, 2018)
Background: Nymphaea spp., Thai water lilies are aquatic plants. They contain phenolic pigments that play a major role in free radical scavenging. Melanoma is strong aggressive skin cancer-associated with oxidative stress. This study, to determine the effect of Nymphaea spp. extracts on cell apoptosis, cellular migration and invasion through the role of cellular oxidants in B16 melanoma cells. Methods: Free radical scavenging activity and total phenolic were investigated by 1, 1-diphenyl-2 picrylhydrazyl (DPPH) and Ferric reducing anti-oxidant power (FRAP) methods and Folin-Denis test, respectively. Cytotoxic were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. Cell apoptosis was confirmed by flow cytometry. Cellular oxidants, cellular migration and invasion were determined with 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA), wound healing and Boyden chamber assay, respectively. Results: Nymphaea pubescens showed higher capacity of scavenging free radical activity than Nymphaea stellate and also related phenolic content. Nymphaea pubescens extract was toxic to B16 melanoma cells. High concentrations cell apoptosis was induced. Contrastingly, low concentrations showed a decrease in cellular oxidants associated with the suppression of cancer cell progression. In B16 melanoma cell, Nymphaea pubescens extract was able to inhibit B16 melanoma cell migration and invasion through the low doses. Interestingly, the high doses of extract showed a potential of cytotoxicity to induce melanoma cell death. At the low doses, Nymphaea pubescens extract might suppress melanoma cells progression by interfering with both cellular migration and invasion capacity. Conclusion: Hence, Nymphaea pubescens extract induced cellular apoptosis and it also suppressed cancer cell progression by reducing oxidative stress in B16 melanoma cells.